Applications of variational iteration and homotopy perturbation methods to fractional evolution equations - Odibat, Zaid; Momani, Shaher (Topological Methods in Nonlinear Analysis, 2008)
In this paper, variational iteration and homotopy perturbation methods that developed for integer-order differential equations are directly extended to derive explicit and numerical solutions of various evolution equations with time-fractional derivatives. The results reveal that the two methods are very effective and convenient for solving nonlinear partial differential equations of fractional order.